Drug Addiction and Its Effect on the Urban Society (Patan Prospective Journal, 2023)
This paper based on the drug addiction and its effect on Urban Society. The aims of the paper are to find out the causes of the drugs addiction and to examine the effect of the drug addiction of the society. It was based on Kritipur Municipality ward no 6 and 7, Bhajungle and Chovar area where the huge numbers of drug users are found and also school children are involved in different types of drug abuse as well as they spend more time in this areas. Sample areas and respondents were selected by the purposive sampling method. The data collection method was primary as well as secondary method. Descriptive research design was used and output of data presented by table and pie chart. Drugs addiction is one of the anti-social activities that goes against everything stand for humanity drug include chemical such as tobacco weed heroine, National Institute on Drug Abuse will harness the new opportunities presented by scientific and technological advances, changes to the health care landscape, ongoing criminal by justice reform and a growing public attention on drug use findings in to real world interventions that can maximize limited resource and reach more people.